2017
DOI: 10.1186/s12889-017-4485-3
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a physical activity program on cardiovascular disease risk in adult primary health-care users: the “Pas-a-Pas” community intervention trial

Abstract: BackgroundPhysical activity is a major, modifiable, risk factor for cardiovascular disease (CVD) that contributes to the prevention and management of CVD.The aim of this study was to assess the short- and medium-term effectiveness of 9 months of a supervised physical activity program, including sociocultural activities, on CVD risk in adults.MethodsMulticentered, randomized, controlled community intervention involving 364 patients in four primary care centers. The participants were randomly assigned to a Contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
53
2
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(61 citation statements)
references
References 35 publications
2
53
2
4
Order By: Relevance
“…Few studies had shown the effect of physical activity on triglycerides [ 19 21 ]. The finding was inconsistent with other studies which have favourable outcomes in at least one of the components of fasting blood glucose and lipid profile [ 22 29 ]. Given the available evidence, we were expecting that the level of fasting blood glucose, total cholesterol or LDL would have some significant decrease in the intervention group, especially among active respondents.…”
Section: Discussioncontrasting
confidence: 87%
“…Few studies had shown the effect of physical activity on triglycerides [ 19 21 ]. The finding was inconsistent with other studies which have favourable outcomes in at least one of the components of fasting blood glucose and lipid profile [ 22 29 ]. Given the available evidence, we were expecting that the level of fasting blood glucose, total cholesterol or LDL would have some significant decrease in the intervention group, especially among active respondents.…”
Section: Discussioncontrasting
confidence: 87%
“…The variables related to the interventions were determined according to previously published studies [35,36]. Two dummy variables were created in a dichotomized fashion: a preintervention period (0) and a postintervention period (1).…”
Section: (Iii)institutional Strategiesmentioning
confidence: 99%
“…The lawsuit data were collected using a form standardized by the researchers after reviewing variables that were investigated in a prior study done in Brazil [30], which included the following: (i) sociodemographic characteristics and the disease(s) of the plaintiffs; (ii) characteristics of the medications solicited in the lawsuits; and (iii) the institutional strategies. The variables related to the interventions were determined according to previously published studies [35,36]. Two dummy variables were created in a dichotomized fashion: a preintervention period (0) and a post-intervention period (1).…”
Section: Variablesmentioning
confidence: 99%